2017
DOI: 10.7150/thno.18125
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Penetrating Theranostic Nanoparticles for Enhancement of Targeted and Image-guided Drug Delivery into Peritoneal Tumors following Intraperitoneal Delivery

Abstract: The major obstacles in intraperitoneal (i.p.) chemotherapy of peritoneal tumors are fast absorption of drugs into the blood circulation, local and systemic toxicities, inadequate drug penetration into large tumors, and drug resistance. Targeted theranostic nanoparticles offer an opportunity to enhance the efficacy of i.p. therapy by increasing intratumoral drug delivery to overcome resistance, mediating image-guided drug delivery, and reducing systemic toxicity. Herein we report that i.p. delivery of urokinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…More recently, efforts were devoted to develop targeted drug delivery system for doxorubicin 58 . Some ingenious systems developed include a chemically crosslinked and functionalized biopolymer dextrin based nanogel 60 ; an anti-CD24 mAb-DOX conjugate via the non-cleavable GMBS (N-[gamma-maleic imide butyl acyl oxygen] succinimide ester) linker 61 ; a metal organic framework nanocarrier-based codelivery system functionalized with folic acid 62 ; a urokinase plasminogen activator receptor targeted magnetic iron oxide nanoparticles 63 ; a double-targeted nondrug delivery system via conjugating hyaluronic acid and grafting the doublecortin-like kinase 1 monoclonal antibody to the surface of PEG-PLGA nanoparticles 64 ; a nucleolin-binding F3 peptide functionalized liposome 65 ; a pH-sensitive triblock copolymer vesicles functionalized with EpCAM monoclonal antibodies 66 ; hyaluronic acid functional amphipathic and redox-responsive polymer particles with a redox-responsive drug release profile 67 ; EpCAM aptamer conjugated PEG-PLGA nanopolymersomes as well as direct aptamer-DOX conjugates 23 , 68 , 69 . These innovations have significantly improved the pharmacokinetics and curtailed toxicity of doxorubicin in the preclinical experimental systems employed.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, efforts were devoted to develop targeted drug delivery system for doxorubicin 58 . Some ingenious systems developed include a chemically crosslinked and functionalized biopolymer dextrin based nanogel 60 ; an anti-CD24 mAb-DOX conjugate via the non-cleavable GMBS (N-[gamma-maleic imide butyl acyl oxygen] succinimide ester) linker 61 ; a metal organic framework nanocarrier-based codelivery system functionalized with folic acid 62 ; a urokinase plasminogen activator receptor targeted magnetic iron oxide nanoparticles 63 ; a double-targeted nondrug delivery system via conjugating hyaluronic acid and grafting the doublecortin-like kinase 1 monoclonal antibody to the surface of PEG-PLGA nanoparticles 64 ; a nucleolin-binding F3 peptide functionalized liposome 65 ; a pH-sensitive triblock copolymer vesicles functionalized with EpCAM monoclonal antibodies 66 ; hyaluronic acid functional amphipathic and redox-responsive polymer particles with a redox-responsive drug release profile 67 ; EpCAM aptamer conjugated PEG-PLGA nanopolymersomes as well as direct aptamer-DOX conjugates 23 , 68 , 69 . These innovations have significantly improved the pharmacokinetics and curtailed toxicity of doxorubicin in the preclinical experimental systems employed.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative imaging using magnetic resonance imaging, computerized tomography, and positron emission tomography are not sensitive enough to detect small tumors (< 7 mm) and tumors smaller than 5 mm are not palpable or visible to surgeons during cytoreductive surgery [3,4]. Studies have shown that hyperthermic intraperitoneal (IP) chemotherapy (HIPEC) following cytoreduction can improve survival outcomes, but this treatment only penetrates a few millimeters into tissue, which may leave behind smaller lesions that may also be resistant to chemotherapy, thereby instigating recurrence [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The recent advent of smart targeted drug delivery has emerged as a promising strategy to overcome these hurdles and enhance therapeutic effects with a minimum of side effects 16 - 21 . Despite promising results in oncology 22 - 24 , the targetable strategy in atherosclerosis has been explored in only a few studies, providing limited benefits such as anti-inflammatory effects 21 , 25 - 27 .…”
Section: Introductionmentioning
confidence: 99%